ЗАСОБИ ЗВíЯЗКУ ЗАПОРІЗЬКОГО КРАЮ У МІЖВОЄННИЙ ПЕРІОД (Zaporizhzhia Historical Review, 2021)
The stages of the communication system development in the South of Ukraine in the intermilitary period are described. On the base of a wide circle of sources the author characterizes the development of the telephone, telegraph nets; he analyses the form and methods of these nets in the ideologized conditions of the totalitarian state.